Experimental and numerical study on seismic behavior of obliquely stiffened steel plate shear walls with openings. (January 2020) - Mu, Zaigen; Yang, Yuqing
Abstract: To study the influence of frame-to-plate connections and oblique channel-shaped stiffeners on the seismic behavior of steel plate shear walls (SPSWs), cyclic quasi-static tests were carried out on two one-bay two-story specimens. One specimen was diagonally stiffened with two rectangular openings, and the other was multi-obliquely stiffened with one rectangular opening. The bearing capacity, ductility, degradation characteristics, and energy dissipation of two specimens were analyzed. Furthermore, following the test program, the stress distribution, deformation and fracture tendency of the two specimens were simulated by the finite element (FE) software ABAQUS and validated by the experimental results. The experimental results show that the channel-shaped stiffeners make full use of the larger flexural and torsional stiffness and improve the bearing capacity, stiffness, and elastic buckling load of the structures. Moreover, the oblique stiffeners have an obvious bracing effect, so the web of the middle beam is subjected to shear yield at the opening segment, which is similar to the link in the eccentrically braced frame. The inelastic mechanism is transferred from the steel plate to the link. In the plastic stage of the structure, the stiffened plate is basically elastic, and the seismic energy is mainly consumed by the link. Therefore, this kind of steel plate shear wall needs to consider the additional effect of the stiffeners on the boundary elements. The reasonable design of the link segment enables the frame to have enough strength to support the stiffened plate as well as avoid premature yielding at the link. Highlights: Steel plate shear walls with oblique channel-shaped stiffeners are proposed. Seismic behaviors of obliquely stiffened steel plate shear walls with openings are studied. Multi-oblique stiffening form can effectively improve the buckling load of plates and delay the formation of tension field. Oblique stiffeners have the bracing effect, making the opening beam segments dissipate the energy like link beams.